Prevalence of major diseases in common marmosets (Callithrix jacchus) at the Central Institute for Medicine and Life Science: a retrospective study - Mineshige, Takayuki; Inoue, Takashi; Yurimoto, Terumi; Sato, Kenya; Kawai, Kenji; Sasaki, Erika (Frontiers in Veterinary Science, 2025)
Common marmosets (Callithrix jacchus) are increasingly being used in neuroscience and biomedical research due to their small size, and ease of handling. Despite their growing research importance, marmoset colonies face health management challenges. Marmoset wasting syndrome (MWS), marmoset duodenal dilatation syndrome (DDS), and Clostridioides difficile-associated disease (CDAD) are the leading causes of mortality in marmosets. We retrospectively analyzed the necropsy records of 192 marmosets based on clinical and pathological criteria at the Central Institute for Medicine and Life Science between 2017 and 2020 to determine the incidence of major diseases and associated treatment modalities. MWS is prevalent in older animals and is characterized by progressive weight loss, hypoalbuminemia, and chronic enteritis. DDS, identified in younger marmosets, is associated with gastrointestinal distress and requires a specialized liquid diet and supportive care. CDAD, which is often triggered by antibiotic administration, leads to sudden death in approximately 68% of cases. This study underscores the need for tailored veterinary care, including early diagnosis, nutritional management, and cautious antibiotic use, to improve marmoset health and reduce mortality rates. Further research on the pathogenesis of these diseases, including gut microbiota analysis, histopathological examination, and diagnostic imaging, is essential for developing effective prevention and treatment strategies.